Analisis Perubahan Penggunaan Lahan Hutan dan Kelapa Sawit Terhadap Penyerapan Co2 di Kabupaten Pasaman Barat - Roky Afandi; Heny Mariati; Novelisa Suryani (Badan Penelitian and Pengembangan (Balitbang), Padang, West Sumatra, Indonesia, 2022)
Changes oh land use from forest into plantations is one of the causes of increased CO2 emissions. The rapid increase in the area of oil palm plantations and the reduction in forest area in West Pasaman Regency will increase greenhouse gas emissions which have a negative impact on the preservation of the earth and its contents. The aims of this study were: to analyze land use changes of forest and oil palm plantations in 1996-2021 and to calculate the total amount of CO2 absorption and emissions caused by changes in forest land use and oil palm plantations in West Pasaman Regency. The research method used is a remote sensing method with the NDVI (normalized difference vegetation index) algorithm for Landsat satellite images. The results showed that there had been a significant change in land use, forest land had decreased by 47,396.39 ha and oil palm land had increased by 105,115.86 ha. Total emissions from changes in forest and oil palm land use are 1,009,411.6 tonnes/ha/year. It is recommended that the Government of West Pasaman Regency need to make a policy to prevent the conversion of forest land into oil palm plantation land. Changes in the use of forest land into plantations is one of the causes of increased CO2 emissions.